2022
DOI: 10.1029/2022ja030507
|View full text |Cite
|
Sign up to set email alerts
|

Energization of Cold Ions in Magnetic Reconnection: Particle‐in‐Cell Simulation

Abstract: Cold ions in the ionosphere can reach the nightside magnetotail along the magnetic field lines, which may substantially affect the magnetotail reconnection and reconnection‐driven phenomena. Although reconnection has been intensively studied in the past decades, the dynamics of cold ions in reconnection are poorly known. We performed a 2.5‐D full kinetic simulation to study the energization of cold ions in a symmetric anti‐parallel reconnection. We find that the cold ions can be considerably energized during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In our simulation, we observe that the dimensionless reconnection rate peaks with E r ∼ 0.09 at t ≈ 18 and becomes quasi‐steady after t ≈ 30 with E r ∼ 0.07 (Song et al., 2023a). However, at t ≈ 55, the reconnection rate begins to decline due to the saturation of the tearing mode caused by the ideal conducting boundary condition.…”
Section: Simulation Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…In our simulation, we observe that the dimensionless reconnection rate peaks with E r ∼ 0.09 at t ≈ 18 and becomes quasi‐steady after t ≈ 30 with E r ∼ 0.07 (Song et al., 2023a). However, at t ≈ 55, the reconnection rate begins to decline due to the saturation of the tearing mode caused by the ideal conducting boundary condition.…”
Section: Simulation Resultsmentioning
confidence: 59%
“…As depicted in Figures 1a and 1b, a robust electric field E z is present at the magnetospheric separatrix region ( z ∼ −1) throughout the reconnection, pointing from the magnetosphere to the magnetosheath ( E z > 0). Previous simulations of asymmetric reconnection have revealed the presence of this electric field (Burch et al., 2016; Dargent et al., 2019; Malakit et al., 2013; Shay et al., 2016; Wang et al., 2017), which is balanced by the Hall term in generalized Ohm's law (Malakit et al., 2013; Song et al., 2023a), indicating that it is a Hall electric field. The magnitude of the Hall electric field E z at t = 50 (Figure 1b) is smaller than that at t = 30 (Figure 1a) and is weaker in the vicinity of the X‐line than in the magnetospheric separatrix region (Figures 1a and 1b).…”
Section: Simulation Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figure 3c shows that the cold ions obtain their energy mainly from the electric field Ez ${E}_{z}$. Interestingly, the out‐of‐plane electric field Ey ${E}_{y}$ does negative work, which is different from symmetric reconnection where cold ions gain energy from the out‐of‐plane electric field Ey ${E}_{y}$ (Divin et al., 2016; Hesse & Birn, 2004; Song et al., 2022). Additionally, the electric field Ex ${E}_{x}$ always does positive work, but its contribution to the cold ion acceleration is much smaller than that by Ez ${E}_{z}$ (Figures 3b and 3c).…”
Section: Cold Ions In Asymmetric Reconnectionmentioning
confidence: 99%
“…Magnetic flux rope is another source of ion acceleration, which can energize ions through the Fermi mechanism when the flux ropes are contracting or merging (Drake et al., 2009). Furthermore, recent simulations have also demonstrated that cold ions can be subject to acceleration through the reconnection electric field in the vicinity of the X‐line (Song et al., 2022). Magnetospheric Multiscale (MMS) observations show that cold ions can be preheated before crossing the Hall electric field layer and heated at the separatrix region at the dayside magnetopause (Toledo‐Redondo et al., 2016).…”
Section: Introductionmentioning
confidence: 99%